2019
DOI: 10.1080/21679169.2019.1571101
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study among women immigrants from Somalia – experiences from primary health care multimodal pain rehabilitation in Sweden

Abstract: Background: Immigrants often experience difficulties with acculturation and post migratory stress after arrival in a host country and studies report poor health, chronic pain and depression. This is a challenge for primary health care and interventions need to be evaluated. Objectives: To explore the experiences of a group of women from Somalia who took part in a multimodal pain rehabilitation programme in primary healthcare in Northern Sweden. Methods: Seven individual interviews a few months after participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…One can see factors such as universality, helping another and hope as being relevant when placing the phenomenon in the framework of group therapy (Kjølstad, 2004). Review studies (Derr, 2016;Semedo et al, 2019) have shown that social support is particularly important for immigrants. The women in the study group, through being part of and belonging to the group, were given the opportunity to experience that they are not alone with their health disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One can see factors such as universality, helping another and hope as being relevant when placing the phenomenon in the framework of group therapy (Kjølstad, 2004). Review studies (Derr, 2016;Semedo et al, 2019) have shown that social support is particularly important for immigrants. The women in the study group, through being part of and belonging to the group, were given the opportunity to experience that they are not alone with their health disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…One can see factors such as universality, helping another and hope as being relevant when placing the phenomenon in the framework of group therapy (Kjølstad, 2004). Review studies (Derr, 2016, Semedo et al, 2019 have shown that social support is particularly important for immigrants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Migrants are considered socially more vulnerable. As patients, they face challenges concerning communication and are at higher risk of experiencing health problems, including mental health illnesses (Ahmed et al, 2017; Bas‐Sarmiento et al, 2017; Semedo et al, 2019). Yet migrants’ overall consumption of different forms of healthcare services is, in many respects, lower than that of the general population (Debesay et al, 2019).…”
Section: Introductionmentioning
confidence: 99%